Gross anatomical syringeal structures of goose (Anser anser domesticus) (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The main purpose of this study was to give detailed information on the position and normal anatomical syringeal structure in goose which had received a little attention in the field of veterinary anatomy.Materials and methods: Six (3 females and 3 males) adult geese weighing 2-4 Kg were used. The goose was slaughtered and its body cavity was opened to detect in situ position of the syrinx. Then the syrinx were dissected and fixed in 10% formaldehyde for 48 h and then kept in 70% ethanol for 2 h.Results: Anatomical examination showed that the syringes of these birds were located in the thoracic cavity at the bifurcation of the trachea. The syrinx was tracheobronchial type formed by tracheosyringeal cartilages, bronchosyringeal cartilages, pessulus, medial and lateral tympaniform membranes, interbronchial ligament and foramen as well as extrinsic syringeal muscles.Conclusion: There were some similarities and some differences of the anatomical structures of the syrinx of goose and that of other bird species. No differences between male and female syrinx were observed.http://doi.org/10.5455/javar.2017.d231